Effects of Integrated Nutrient Management on Growth, Nodulation, and Yield of Soybean [Glycine max (L.) Merr. var. Puja] - Sudarshan Khanal; Madhab Bhattarai; Babin Kharel; Manoj K.C; Dipesh Chand Yadav; Achyut Gaire; Chhaya Khanal; Rajendra Bam (AgroEnvironmental Sustainability)
Inefficient fertilizer management is a major reason for the low soybean productivity in Nepal. This study conducted at an altitude of 811 meters in Baitadi, Nepal, examined the effects of integrated nutrient management on soybean growth, nodulation, and yield. Employing an RCBD experimental layout with 3 replications, the study evaluated 9 treatments, namely: Control, Rhizobium+100% PK, Rhizobium+50% RDF, Rhizobium+75% RDF, Vermicompost+50% RDF, Vermicompost+75% RDF, FYM+50% RDF, FYM+75% RDF, RDF (NPK @ 10:40:30 kg/ha). The results revealed that ‘Rhizobium+100% PK’ produced maximum plant height (140.8 cm), dry weight growth rate (2.89 gram/plant/day), nodule count (11.33), and nodule mass (0.55 gram). ‘Rhizobium+75% RDF’ produced the highest number of trifoliate leaves (62.78) and leaf area index (15.30). Furthermore, ‘Vermicompost+50% RDF’ resulted in a maximum fresh weight growth rate (7.86 gram/plant/day), ‘RDF’ resulted in the highest root diameter (12.89 mm), and ‘FYM+75% NPK’ produced highest 1000-grain weight (145.9 g). The treatments ‘VC+75 % RDF’ and ‘Rhizobium+50 % RDF’ stood out with a remarkable grain yield of 3.659 tons/ha and 3.642 tons/ha respectively. These two treatments were statistically indistinguishable regarding grain yield. The application of ‘VC+75 % RDF’ or ‘Rhizobium+50 % RDF’ can prove to be an effective way to enhance the productivity of soybean. However, the performance of soybean can vary depending on the variety, intercultural operations, environmental conditions, and residual nutrient status of the soil. Therefore, we recommend further research to solidify these findings.